UX strategy : how to devise innovative digital products that people want. - Levy, Jaime (O'Reilly Media, Inc, USA, 2021)
"User experience (UX) strategy lies at the intersection of UX design and business strategy, but until now, there hasn't been an easy-to-apply framework for executing it. This hands-on guide introduces lightweight product strategy tools and techniques to help you and your team devise innovative digital solutions that people want.Author Jaime Levy shows UX/UI designers, product managers, entrepreneurs, and aspiring strategists simple to advanced methods that can be applied right away. You'll gain valuable perspective through business cases and historical context. This second edition includes new real-world examples, updated techniques, and a chapter on conducting qualitative online user research.Define value propositions and validate target users through provisional personas and customer discovery techniques. Explore marketplace opportunities by conducting competitive research and analysis. Design experiments using rapid prototypes that are focused on the business model. Conduct online user research to gain valuable insights quickly on any budget. Test business ideas and validate marketing channels by running online advertising and landing page campaigns."